Evaluating the contribution of integrated mine closureand post- closure in realising the United Nations' Sustainable Development Goals - Gerber, Leonardus J. (University of Pretoria, 2023)
Thesis (LLM (Extractive Industry law in Africa))--University of Pretoria, 2023.